2021
DOI: 10.1155/2021/1092975
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dendrobium Polysaccharides on the Functions of Human Skin Fibroblasts and Expression of Matrix Metalloproteinase-2 under High-Glucose Conditions

Abstract: The effects of Dendrobium polysaccharides (PDC) on the functions of human skin fibroblasts (HSFs) and expression of matrix metalloproteinase-2 under high-glucose conditions and exploration of the underlying mechanism remain unclear. We used the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) analysis and flow cytometry to evaluate the cell viability and apoptosis. The collagen levels were determined by the Sircol™ Collagen Assay. Real-time quantitative polymerase chain reaction (RT-PCR) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(43 reference statements)
1
2
0
Order By: Relevance
“…Recently, these studies revealed that PDC at the concentrations of 100, 200, as well as 400 mg/mL elevates the level of COL, improves the viability of human skin fibroblasts, suppresses the cell apoptosis induced by HG, accompanied by the elevation of TIMP-2 and reduction of MMP-2. Therefore, these results confirmed that PDC can display protective effects on diabetic ulcer in vitro, and the mechanism may be related to the modulation of TIMP-2 and MMP-2, which provides a new idea for the prevention and treatment of diabetic skin ulcer or wound (98). However, further in vivo researches are required to clarify the activity of PDC against diabetic wound healing.…”
Section: Polysaccharide and Glucosidesupporting
confidence: 58%
“…Recently, these studies revealed that PDC at the concentrations of 100, 200, as well as 400 mg/mL elevates the level of COL, improves the viability of human skin fibroblasts, suppresses the cell apoptosis induced by HG, accompanied by the elevation of TIMP-2 and reduction of MMP-2. Therefore, these results confirmed that PDC can display protective effects on diabetic ulcer in vitro, and the mechanism may be related to the modulation of TIMP-2 and MMP-2, which provides a new idea for the prevention and treatment of diabetic skin ulcer or wound (98). However, further in vivo researches are required to clarify the activity of PDC against diabetic wound healing.…”
Section: Polysaccharide and Glucosidesupporting
confidence: 58%
“…This finding is in accordance with those obtained in previous research, where it has been reported that the Morin-incorporated polysaccharide-protein hydrogel accelerates diabetic wound healing in Wistar rats [ 39 ]. In addition, Li et al [ 43 ] demonstrated that polysaccharides extracted from Dendrobium candidum could be a potential candidate as wound healing-accelerating agents thanks to their incredible wound healing properties in both in vitro and in vivo experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Set the temperature constantly of the water bath to 37°C for 40 min, add the color reagent and mix well, pour it into a 1 cm optical path cuvette after 10 min, adjust to zero with distilled water, and compare the color with a microplate reader at a wave length of 550 nm. According to the formula SOD activity ðU/mgprotÞ = ½ðcontrol tube − measurement tubeÞ/control tube ÷ 50% × ðtotal volume of reaction solution /sampling amountÞ ÷ protein content in tissue ðmgprot/mLÞ, to calculate SOD activity, no clear sample is added to the control tube, and the others are the same as the measurement tube [13][14][15].…”
Section: Tetrazolium Blue Colorimetric (Mtt) Methods Was Usedmentioning
confidence: 99%